Selection of Appropriate Biogas Upgrading Technology-A Review of Biogas Cleaning, Upgrading and Utilisation (International Journal of Innovative Research in Computer Science & Technology, 2021)
Biogas is going through a time of  tremendous growth, and biogas upgrading is getting a lot  of attention. As a consequence, the biogas upgrading  business has significant challenges in terms of energy  consumption and operating costs. The technique of  upgrading is determined on a site-by-site, case-by-case  basis, and depending on biogas consumption requirements and local variables. Like a reason, it's  crucial to match the technology used to specific  requirements. The current state of biogas cleaning and  upgrading technologies is investigated, comprising  product purity and pollutants, methane recovery as well  as loss, upgrading efficiency, and capital and operational  costs. Furthermore, the potential usage of biogas, as well  as the consequent gas quality requirements, are fully  investigated. The outcomes of comparisons between both  the technical features of upgrading technologies, the  specific demands for different gas usage, as well as the  corresponding investment and operating costs are used to  provide suggestions for appropriate technology.
Keywords: Biogas; Bio-Oil; CO2; Cleaning; Technology